Business literacy classes for enhancing Nepalese women’s access to knowledge, skills and resources - Rai, Renuka; Thapa, Krishna (Technical Centre for Agricultural and Rural Cooperation, 2018)
Business literacy classes are addressing the knowledge gaps between men and women in Nepal, and developing the business-related knowledge and skills of women commercial farmers. Not only has this intervention improved women’s confidence when establishing agribusinesses, but their involvement in decision-making within producer organisations and households has also positively increased.